Feasibility of Using Marshall Criteria into Public Relations by the Librarians of Arak and Isfahan University of Medical Sciences - Ahmad Shabani; Akram Moslemi; Rasul saadat (Iranian Journal of Information Processing & Management, 2014)
This research aims to survey the use rate of Marshall criteria into public relations by the librarians of Arak and Isfahan University of Medical Sciences. It was used the survey-descriptive method respectively. In order to gathering the research data it was used a researcher-made questionnaire; this measured the use rate of 7 Marshall criteria (Budgeting, financial resources and gifts, informing the faculties and students, the more use of the library by the university people, improving the general viewpoint of academic community to the library, informing the non-academic community, and the more use of the library by the non-academic community) into public relations. The population included the librarians in the above mentioned universities out of which 86 ones sampled. For the validity, the viewpoints of experts were applied into the questionnaire. For the reliability Cronbach's alpha coefficient was calculated .987. In order to data analysis the SPSS 16 was used. The findings showed that in opinion of the librarians, applying of the public relations into 7 Marshall criteria was relatively favorable. In order to improving the conditions, experts should hold the educational courses on Public Relations